Synthesis, antioxidant, and antimicrobial evaluation of novel 2,3-dihydro-1H-pyrazole-4-carbonitrile derivatives using K2CO3/glycerol as a green deep eutectic solvent - Zwain, Ali A.; Ahmad, Irfan; Khalaf Jebur Ali, Rasha; Kahtan, Mustafa; Khdyair Hamad, Atheer; Abdulgader Hassan, Enas; Asiri, Mohammed; Ridha, Benien M.; Alsalamy, Ali (Frontiers in Materials, 2023)
Abstract: Through the multi-component reaction of aldehyde derivatives, methyl 2-cyanoacetate, and phenylhydrazine using K2CO3, and glycerol as a deep eutectic solvent, new derivatives of 2,3-dihydro-1H-pyrazole-4-carbonitrile were synthesized. The structure of the newly synthesized compounds was confirmed using 1H NMR, 13C NMR, and elemental analysis. Biological evaluation of the synthesized 2,3-dihydro-1H-pyrazole-4-carbonitrile derivatives, including antioxidant activity on DPPH free radical and antimicrobial activity on a wide range of Gram-negative, Gram-positive bacte-rial, and fungal species, was done. The antioxidant activity, IC50, and antimicrobial activity were as-sessed through IZD, MIC, MFC, and MBC parameters. 2,3-dihydro-1H-pyrazole-4-carbonitrile deriv-atives showed significant antioxidant and antibacterial activity and, in examining the results, a good relationship between the structure and biological activity of the 2,3-dihydro-1H-pyrazole-4-carbonitrile derivatives were found.